SOSIAL MEDIA SARANA PROMOSI PADA PEDAGANG PAKAIAN DI PASAR SUDIMAMPIR BANJARMASIN - Ariyadi Ariyadi (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2019)
The rise of promotions and buying-selling through internet where social media has become one of the media, it has many positive impacts, such as buying-selling transactions have become easier. Meanwhile, it has negative impacts too, such as fraud and others, this makes researchers interested in researching how clothing traders on the Sudimampir market, Banjarmasin utilizes media as a promotion in order to be able to compete and increase their sales. This research aims to find out how the use of social media in clothing in Sudimampir market, as well as the obstacles that faced when using social media as a means of promotion.The researcher used field research, which is descriptive qualitative by conducting in-depth interviews and then the results can be summarized. The informants in this study were 15 people, all of whom were clothing traders who were selling in the Sudimampir market.The results of this study indicate that the use of social media as a promotion of clothing Sudimampir market using several social media such as: WA (Whatsapp), BBM (Blackberry Messenger), FB (Facebook). Those social media used as a means for ordering, Facebook and Instagram used for uploading photos of the items they sell. Those social media give a positive impact, namely their sales have increased which is in accordance with the function of social media in trading, which can increase sales.